Preparatory review of studies of withdrawal of anti-hypertensive medication in older people - Harrison, Jennifer K.; Gladman, John R.F.; van der Wardt, Veronika; Conroy, Simon (University of Nottingham, 2015)
Introduction: Since 2012 we have undertaken a programme of research into the management of hypertension in people with dementia. As part of this we are studying the feasibility of withdrawing antihypertensive drugs in people with dementia and well-controlled hypertension, with the aim of them remaining normotensive but avoiding some of the burdens and side-effects of antihypertensive medications. We decided to undertake a preliminary examination of the literature to examine the evidence and safety of antihypertensive withdrawal (not restricted to those with dementia) to determine whether this has already been extensively reviewed, to provide an approximate estimate of the likelihood of success of antihypertensive withdrawal, and to prepare for a systematic review of this literature if required and feasible. Method: For this rapid review, we undertook a search for existing reviews and examined the relevant papers identified, and briefly updated the search once we found that the most recent review was in 2008. Results: One appropriate review (from 2008) yielding seven relevant articles, and one further article were identified, giving eight articles which were examined. Seven of the eight were published more than ten years ago. Six of the eight studies had follow-up data for 1 year or longer. Successful long term (1 year or more) withdrawal of antihypertensive medication was reported in 20-52% of patients. Conclusion: Our review indicates that 22-50% of patients whose blood pressures are currently adequately controlled might be able to withdraw medication without return of long term hypertension. The rapid review approach we took may have missed articles of relevance and so we propose that a systematic review of withdrawal is undertaken. Because much of the data will be old, it should seek data not only on the proportions of patients who remained normotensive at long term follow up using the standards of the day, but should seek data on findings relevant to current guidelines. Only data reporting long term follow up (≥ 1 year) should be included. Data referring to old or discontinued medications should be distinguished.